Symbolic Interactionism in Ceremonies of Ritual Medicine in Malay Society in Riau Province - Nurmalinda Nurmalinda (Journal of Urban Society's Arts, 2022)
The purpose of this study is to describe the symbolic interactions in the ritual ceremonies of medical treatment in Riau Province and the symbolic meanings of ritual ceremonies in the Malay community in Riau Province. This study uses descriptive qualitative methods. The medical rituals in Riau province studied include Kuantan, Bedikie, Menyemah, Pole, Cabut Kelo, Talam Muka Dua, Bokuan, and Buang Badi. These rituals are procedures for a medical ceremony carried out by a group of people in Riau Province, marked by the presence of several elements and components, namely the existence of time, the place of the ceremony, the ceremonial instruments, and the people who performed the ceremony. The study of symbolic interactionism in ritual ceremonies of the Malay community focuses on interactions that give rise to special meanings that create interpretation. The symbols used in the ceremonies result from mutual agreements. How things become a shared perspective and how an action gives special meanings can only be understood by those who perform the ceremonies. Mulyana’s symbolic interaction theory points out that self, social self, including control from other people’s perspectives, interpretations, and other meanings that appear in the interaction form three premises (1) humans act based on meanings; (2) meanings derive from interaction with others, (3) meaning develops and refines when interactions take place. Interaksionisme Simbolik Upacara Ritual Pengobatan dalam Masyarakat Melayu di Provinsi Riau. Penelitian ini bertujuan untuk mendeskripsikan  interaksi simbolik dalam upacara-upacara ritual pengobatan di Provinsi Riau dan makna simbol upacara-upacara ritual pengobatan kepada masyarakat Melayu di Provinsi Riau. Penelitian ini menggunakan metode kualitatif jenis deskriptif. Ritual pengobatan yang terdapat di Provinsi Riau yang diteliti di antaranya Kumantan, Bedikie, Menyemah, Pole, Cabut Kelo, Talam Muka Dua, Bokuan, dan Buang Badi. Ritual-ritual ini merupakan tata cara dalam upacara pengobatan yang dilakukan oleh sekelompok masyarakat di Provinsi Riau, ditandai dengan adanya beberapa unsur dan komponen, yaitu adanya waktu, tempat upacara dilakukan, alat-alat upacara, serta orang-orang yang melakukan upacara. Kajian interaksionisme simbolik dalam upacara ritual masyarakat Melayu menitikberatkan pada interaksi yang memunculkan makna-makna khusus yang melahirkan interpretasi. Simbol-simbol yang digunakan dalam upacara-upacara tersebut merupakan hasil kesepakatan bersama. Bagaimana suatu hal menjadi perspektif bersama dan bagaimana suatu tindakan memberikan makna khusus hanya dapat dipahami oleh orang-orang yang melakukannya. Teori interaksi simbolik Mulyana menyatakan bahwa diri, diri sosial, termasuk kontrol dari sudut pandang orang lain, interpretasi, dan makna lain yang muncul dalam interaksi membentuk tiga premis (1) manusia bertindak berdasarkan makna; (2) makna berasal dari interaksi dengan orang lain, (3) makna berkembang dan disempurnakan ketika interaksi berlangsung.